Incidence of Temporomandibular Joint Disorders in Patients with Malocclusion - KAMEI, Teruaki; AKIMOTO, Susumu; SATO, Sadao; FUSHIMA, Kenji; TAKAMOTO, Kenyu; SUZUKI, Yoshii (Journal of the Japanese Society for the Temporomandibular Joint, 1989)
In order to examine the relationship between the incidence of temporomandibular joint (TMJ) disorders and the occlusal problems, epidemiological surveys regarding the signs of TMJ disorders (joint noise, pain and disturbance of mandibular movement) were carried out to 149 untreated patients (54 males and 95 females) with malocclusion. The results indicated as follows: 1) Incidence of TMJ disorders was 33.6% of total samples, 27.8% of males and 36.8% of females. 2) In symptomatic subjects, the most fregent sign of TMJ disorders was joint noise (76.0%), the second was joint pain (68.0%) and the third was disturbance of mandibular movement (38.0%). 3) The incidence of TMJ disorders increased after 8 years of age, while it decreased slightly from 15 to 18 years of age and showed high frequency after 19 years of age. It was suggested that these changes were related with the occlusal configurations such as the exfoliation followed by the eruption of permanent successors or the eruption of the third molars. 4) Symmetrical anterior cross-bite malocclusion showed low incidence of TMJ disorders. In posterior cross-bite malocclusion and mandibular lateral displacement case, however, the signs of TMJ disorders were found frequently. These results suggested that the lateral shift of mandibular head in fossa may relate with the appearance of TMJ disorders.